2018
DOI: 10.3390/cosmetics5010008
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Spin Traps to Control ROS in Antipollution Cosmetics—A Review

Abstract: Abstract:Pollution from air and sunlight has adverse effects on human health, particularly skin health. It creates oxidative stress, which results in skin diseases, including skin cancer and aging. Different types of antioxidants are used as preventative actives in skin-care products. However, they have some limitations as they also scavenge oxygen. Recently, spin traps are being explored to trap free radicals before these radicals generating more free radicals (cascading effect) and not the oxygen molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…As the best known role of nitrones is to scavenge anion superoxide and hydroxyl radicals, they are sometimes classified as antioxidant therapeutics proposed for a wide variety of medicinal indications and have been used for therapy of various conditions such as neurodegeneration, cardiovascular disease, stroke, and cancer [13,14], in antipollution cosmetics, noise-induced neural degeneration, elimination of nociceptive behavior, and for the protection of retina from light-induced damage [14–17]. Differences in the activity of spin-traps and classical antioxidants (enzymatic or nonenzymatic) are that the latter may indiscriminately convert both normal oxygen and ROS molecules to water alone, leading to deep tissue hypoxia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the best known role of nitrones is to scavenge anion superoxide and hydroxyl radicals, they are sometimes classified as antioxidant therapeutics proposed for a wide variety of medicinal indications and have been used for therapy of various conditions such as neurodegeneration, cardiovascular disease, stroke, and cancer [13,14], in antipollution cosmetics, noise-induced neural degeneration, elimination of nociceptive behavior, and for the protection of retina from light-induced damage [14–17]. Differences in the activity of spin-traps and classical antioxidants (enzymatic or nonenzymatic) are that the latter may indiscriminately convert both normal oxygen and ROS molecules to water alone, leading to deep tissue hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the activity of spin-traps and classical antioxidants (enzymatic or nonenzymatic) are that the latter may indiscriminately convert both normal oxygen and ROS molecules to water alone, leading to deep tissue hypoxia. Spin-traps react with the ROS by intercepting it before any damage is done and PBN seems to be the least toxic of nitrones [14]. PBN itself was able to act preventively and/or therapeutically in rat models of glioma, the choline deficiency liver cancer model, and the mouse APCMin/+ colon cancer model [13] and it can probably act similarly on other malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the skin is an important organ that protects us from the environment. For this reason, it is necessary to ensure the skin health also by using cleansers, which are surfactants used to reduce sebum, remove make-up residuals or exogenous contaminants such as sweat, pollution or dirt, and promote normal exfoliation [233][234][235][236][237]. However, the repeated and prolonged interaction between these surfactants and the proteins or lipids of stratum corneum could weaken the skin barrier function.…”
Section: Skin Cleanersmentioning
confidence: 99%
“…Free radicals cause oxidative damage to different molecules, such as lipids, proteins and nucleic acids and thus are involved in the initiation phase of some degenerative diseases . Research has shown that free radical mediated oxidative stress is among the major causative factors in induction of many chronic and degenerative diseases including atherosclerosis, ischemic heart disease, ageing, diabetes mellitus, cancer, immunosuppression, neurodegenerative diseases and others 60,61 .…”
Section: Total Antioxidant Capacity (Tac)mentioning
confidence: 99%